Formulation of Cefdinir Ternary Solid Dispersion and Stability Study under Harsh Conditions - Naamaa A. Naama; Ghaidaa S. Hameed; Dalya Basil Hanna; Zainab H. Mahdi (Al-Mustansiriyah Journal of Pharmaceutical Sciences)
Cefdinir (CEF) is classified as a third-generation cephalosporin within class IV of the Biopharmaceutical Classification System (BCS). Cefdinir has low solubility and permeability, which may reduce oral bioavailability.